1T′‐ReS2 Confined in 2D‐Honeycombed Carbon Nanosheets as New Anode Materials for High‐Performance Sodium‐Ion Batteries. Issue 30 (7th July 2019) - Chen, Biao; Li, Huan; Liu, Huaxiong; Wang, Xinqian; Xie, Fangxi; Deng, Yida; Hu, Wenbin; Davey, Kenneth; Zhao, Naiqin; Qiao, Shi‐Zhang
Abstract: ReS2 (rhenium disulfide) is a new transition‐metal dichalcogenide that exhibits 1T′ phase and extremely weak interlayer van der Waals interactions. This makes it promising as an anode material for sodium‐ion batteries. However, achieving both a high‐rate capability and a long‐life has remained a major research challenge. Here, a new composite is reported, in which both are realized for the first time. 1T′‐ReS2 is confined through strong interfacial interaction in a 2D‐honeycombed carbon nanosheets that comprise an rGO inter‐layer and a N‐doped carbon coating‐layer (rGO@ReS2 @N‐C). The strong interfacial interaction between carbon and ReS2 increases overall conductivity and decreases Na + diffusion resistance, whilst the intended 2D‐honeycombed carbon protective layer maintains structural morphology and electrochemical activity during long‐term cycling. These findings are confirmed by advanced characterization techniques, electrochemical measurement, and density functional theory calculation. The new rGO@ReS2 @N‐C exhibits the greatest rate performance reported so far for ReS2 of 231 mAh g −1 at 10 A g −1 . Significantly, this is together with ultra‐stable long‐term cycling of 192 mAh g −1 at 2 A g −1 after 4000 cycles. Abstract : 1T′‐ReS2 confined in 2D‐honeycombed carbon nanosheets is reported as a promising sodium‐ion battery anode with ultra‐stable long term cycling and high rate performance. High rate performance is attributed to strong interfacial interaction between carbon and ReS2 and the intended 2D‐honeycombed carbon protective layer. Findings are corroborated by advanced characterization techniques and theoretical calculations.